A ROLE OF DIACYLGLYCEROL KINASE IN STIMULUS-SECRET I ON COUPLING OF HUMAN PLATELETS -DISSOCIATION OF SEROTONIN SECRETION FROM Ca2+ MOBILIZATION- - TOHMATSU, T; NAKASHIMA, S; HATTORI, H; SUGANUMA, A; NOZAWA, Y (Thrombosis and Haemostasis, 1987)
Diacylglycerol (DG) kinase catalyzes the reaction: DG + ATP phosphatidic acid + ADP and it is widely distributed in animal tissues. The enzyme seems to play a pivotal role in removing a second messenger, DG, which activates protein kinase C. DG kinase inhibitor, R 59 022 (6-[2-[4-[(4-fluorophenyl)pheny1- methylene] -1-piperidinyl] ethyl] -7-methyl-5H-thiazolo [3,2-a] -pirimidin-5-one) has recently been developed. In order to gain further insight into the role of DG in the secretory response, effects of the DG kinase inhibitor on secretory responses and Ca2+ mobilization were investigated in human platelets.The addition of the DG kinase inhibitor (10 μM) potentiated thrombin-induced accumulation of [3H]radioactivity of DG in platelets loaded with [3H] arachidonate. Thrombin-induced release of [3H] arachidonic acid and its metabolites was not affected by the inhibitor. The inhibitor did not cause significant secretion of [14C] serotonin by itself. However, the pretreatment with this agent potentiated the level of secretion in thrombin-stimulated platelets. When l-oleoyl-2-acetylglycerol(OAG) was added to [32pjpi-iabeled platelets in the presence of the DG kinase inhibitor, the formation of [32P] l-oleoyl-2-acetylphosphatidic acid was greatly prevented. The pretreatment with the inhibitor also potentiated OAG-induced serotonin secretion. With the view that Ca2+ is thought to be another important second messenger, we investigated the effect of the DG kinase inhibitor on Ca2+ mobilization. Two types of Ca2+ indicators, Quin2 and aequorin were used to measure cytosolic free Ca2+ concentration ([Ca2+]i). The inhibitor alone did not affect [Ca2+]i. Interestingly, thrombin-induced increase in [Ca2+]i was suppressed by the pretreatment with this agent both in the Quin2-loaded and aequorin-loaded platelets.These results indicate that diacylglycerol kinase may operate as an attenuator in the signal transduction system involving protein kinase C and that Ca2+ mobilization may not be tightly coupled to serotonin secretion.